Neuropathology of COVID-19: a spectrum of vascular and acute disseminated encephalomyelitis (ADEM)-like pathology - Reichard, R. Ross (Acta Neuropathol, 2020)
We report the neuropathological findings of a patient who died from complications of COVID-19. The decedent was initially hospitalized for surgical management of underlying coronary artery disease. He developed post-operative complications and was evaluated with chest imaging studies. The chest computed tomography (CT) imaging results were indicative of COVID-19 and he was subsequently tested for SARS-CoV-2, which was positive. His condition worsened and he died after more than 2 weeks of hospitalization and aggressive treatment. The autopsy revealed a range of neuropathological lesions, with features resembling both vascular and demyelinating etiologies. Hemorrhagic white matter lesions were present throughout the cerebral hemispheres with surrounding axonal injury and macrophages. The subcortical white matter had scattered clusters of macrophages, a range of associated axonal injury, and a perivascular acute disseminated encephalomyelitis (ADEM)-like appearance. Additional white matter lesions included focal microscopic areas of necrosis with central loss of white matter and marked axonal injury. Rare neocortical organizing microscopic infarcts were also identified. Imaging and clinical reports have demonstrated central nervous system complications in patients’ with COVID-19, but there is a gap in our understanding of the neuropathology. The lesions described in this case provide insight into the potential parainfectious processes affecting COVID-19 patients, which may direct clinical management and ongoing research into the disease. The clinical course of the patient also illustrates that during prolonged hospitalizations neurological complications of COVID may develop, which are particularly difficult to evaluate and appreciate in the critically ill.